Technical Diversity in Contemporary Kurdish Art - misanjas misanjas; Sirwan Rafat Ahmed ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
The aim of the current research is to highlight the representations of technical diversity in contemporary Kurdish visual arts. The original research community included the artworks of 20 Kurdish artists from the Kurdistan Region of Iraq. Artistic works for each artist were collected from various sources, such as magazines, social media platforms, and the official websites of the artists, resulting in 5 artworks for each artist. The selected samples for the research consisted of 3 models chosen intentionally based on the following justifications:The diversity of technical performance in the selected sample models.The selection of models that have a clear and distinctive presence both locally and globally.After studying the technical diversity, the researcher concluded that this diversity plays an effective role in the performance and variety of artistic works concerning form and technique.